Maize Yield Response to Nitrogen Rates and Sources Associated with Azospirillum brasilense - Galindo, Fernando S. [UNESP]; Teixeira Filho, Marcelo C. M. [UNESP]; Buzetti, Salatier [UNESP]; Pagliari, Paulo H.; Santini, Jose M. K. [UNESP]; Alves, Cleiton J. [UNESP]; Megda, Marcio M.; Nogueira, Thiago A. R. [UNESP]; Andreotti, Marcelo [UNESP]; Arf, Orivaldo [UNESP] (Amer Soc Agronomy, 2019)
New studies are needed to optimize the nitrogen amount that can be applied to utilize the Azospirillum brasilense benefits in maize cropping systems. In addition, information regarding the interaction between the urease inhibitor N-(n-butyl) thiophosphoric triamide (NBPT) and biological nitrogen fixation (BNF) and how they affect the crop development and yield is also needed. The objective of this study was to evaluate the effect of rates and sources of N in combination with A. brasilense, on leaf chlorophyll index (LCI), N leaf concentration, production components, and maize grain yield in the Brazilian Cerrado region. The study was performed in a Typic Rhodic Hapludox under no-tillage system. The experimental design was a randomized complete block design with four replications arranged in a 2 x 5 x 2 factorial scheme: two N sources (urea and urea with NBPT) and five N rates (0, 50, 100, 150, and 200 kg ha(-1)), with and without A. brasilense inoculation. The increase in N rates significantly enhance LCI, N leaf concentration, plant height, ear diameter, mass of 100 grains, and grain yield. No significant differences were observed among the N sources. Inoculation with A. brasilense increased LCI, stem diameter, ear length, and nitrogen use efficiency (NUE), with a positive effect on grain yield. The increase in N rate up to 200 kg ha(-1) with A. brasilense inoculation increased grain yield, independently of the N source. The application of 100 kg ha(-1) of N as urea, with inoculation of A. brasilense produced the highest profit in maize production.